Implementation of Public Service Standards Based on Law in Indonesia - Muhammad Amalan Pasaribu; Osama Bhinneka Pulungan (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
The implementation of public service standards in Indonesia is a crucial part of efforts to realize effective, transparent, and accountable governance. Public service standards are regulated in Law Number 25 of 2009 concerning Public Services, which serves as a guideline for every service provider in providing quality services to the public. This study aims to examine the implementation of public service standards based on statutory provisions and identify various obstacles encountered in their implementation. The method used in this research is a normative legal approach by examining various laws and regulations, literature, and concepts related to public services. The results of the study indicate that normatively, public service standards have covered important aspects such as service procedures, completion time, costs, service products, facilities and infrastructure, and implementer competence. However, in practice, various problems are still found, including limited human resources, lack of supervision, suboptimal use of technology, and low public participation in the service evaluation process. Furthermore, there is a disparity in service quality between urban and remote areas, indicating uneven implementation of public service standards. Therefore, efforts are needed to increase the capacity of civil servants, strengthen oversight systems, and innovate in information technology-based services. This is expected to ensure optimal implementation of public service standards, increase public trust in the government, and ensure the fulfillment of community rights fairly and equitably.